2018
DOI: 10.1186/s12916-018-1163-y
|View full text |Cite
|
Sign up to set email alerts
|

Specific microRNA signatures in exosomes of triple-negative and HER2-positive breast cancer patients undergoing neoadjuvant therapy within the GeparSixto trial

Abstract: BackgroundThe focus of this study is to identify particular microRNA (miRNA) signatures in exosomes derived from plasma of 435 human epidermal growth factor receptor 2 (HER2)-positive and triple-negative (TN) subtypes of breast cancer (BC).MethodsFirst, miRNA expression profiles were determined in exosomes derived from the plasma of 15 TNBC patients before neoadjuvant therapy using a quantitative TaqMan real-time PCR-based microRNA array card containing 384 different miRNAs. Forty-five miRNAs associated with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
144
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 151 publications
(145 citation statements)
references
References 47 publications
1
144
0
Order By: Relevance
“…Differential expressions of subtype-specific miRNAs have also been reported in several studies [27,37] . Eichelser et al [27] analyzed circulating cell-free and exosomal miR-101, miR-372, and miR-373 in preoperative blood serum.…”
Section: Diagnostic Potentials Of Exosomal Micrornasmentioning
confidence: 58%
See 2 more Smart Citations
“…Differential expressions of subtype-specific miRNAs have also been reported in several studies [27,37] . Eichelser et al [27] analyzed circulating cell-free and exosomal miR-101, miR-372, and miR-373 in preoperative blood serum.…”
Section: Diagnostic Potentials Of Exosomal Micrornasmentioning
confidence: 58%
“…There have been few studies concerning the association between exosomal miRNAs and treatment efficacy in the clinical setting. We found one article by Stevic et al [37] on this topic. They analyzed several exosomal miRNAs which were determined based on analysis with a microRNA array card using the patients' plasma samples before neoadjuvant therapy (GeparSixto trial).…”
Section: Resistance To Chemotherapy and Molecular-targeted Therapymentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, exosomal miRNAs could serve as monitoring indicators for therapeutic response. Stevic et al 68 found that 17 miRNAs in 224 TNBC patients who underwent neoadjuvant therapy were significantly deregulated, which were significantly associated with the clinic‐pathological and risk factors. To sum up, as a novel hotspot of cancer research, exosome‐mediated miRNAs may act as multiple roles in TNBC, which should be further explored in the future.…”
Section: Micrornasmentioning
confidence: 99%
“…There also several studies to investigate the exosomal miRNA expression profiles in order to screen crucial exosomal miRNAs for breast cancer progression. However, most of them focused on chemoresistance mechanisms in breast cancer cells [14,15] or biomarker screening in serum or plasma of patients [16][17][18]. In the present study, we aimed to identify exosomal differentially expressed miRNAs (DEMs) between breast cancer cells and normal control cells by comprehensive analysis of two microarray datasets downloaded from the public Gene Expression Omnibus (GEO) database.…”
Section: Introductionmentioning
confidence: 99%